poetics of Eevhen Hrebinka’s poem “Bohdan”: (anti)colonial strategies of the art CONSCIOUSNESS - Olga V. Shaf; Oleksandra V. Goniuk (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
Evhen Hrebinka’s oeuvre, particularly his Russian-language works and the poem “Bohdan” (1843), have not been studied well. The theme of this historical poem is Bohdan Khmelnytskyi’s decision to get political protection from the Tsardom of Muscovy. (Anti-)colonial moods of art implementation of this theme can be rethought with the help of a postcolonial approach. It is important to recognize the influence of psychical and mental backgrounds in the author’s consciousness and literary aesthetics onto the juxtaposition of anti-colonial and colonial art thinking in the 19th century Ukrainian literature in general, and Hrebinka’s works in particular. Purpose of the article. The article seeks to study (anti-)colonial poetics in Evhen Hrebinka’s poem “Bohdan” through the view of the author’s consciousness as well as through Romanticism art and aesthetical paradigm in intertextual relations with Ukrainian romantic historical literature. The article employs techniques of postcolonial deconstruction (the methodology is based on Russian imperialism studies by E. Tompson, M. Shkandrii, O. Yurchuk grounded in the West postcolonialism theory), intertextological and other literary analysis methods. Evhen Hrebinka’s poem “Bohdan” as well as his other Russian-language works have not been appropriately read because of its ideological points. In the view of postcolonialism, the balancing between imperial and Ukrainophilical narratives is the symptom of deformation of mental (art) consciousness under cultural and political imperial pressing, which is shown in the oeuvre of Hrebinka and his contemporaries. On the one hand, the appreciation of the past in the works of Ukrainian writers, particularly Hrebinka, was shaped by Russian historiographical doctrine which negotiated the state-creating capacity of Cossack Hetmanate leaders and spread fakes about “one-blood nations”, “happy life under the reign of Tsar of Muscovy”, and on the other hand, their reception of the Cossack history was steered by romantic anti-colonial resentment. This ambiguity determines the poetics of the poem “Bohdan” by Evhen Hrebinka. In the poem, on the discursive level of writing both pro-imperial and pro-national creative intentions are evident. Their counterposition is most prominent in the collision of the historical (Chapters 1-9) and mythopoetic (the Prologue) plans of the poem. In the historical plot (Chapters 1-9), the neocolonial idea of agreement with Moscow`s imperial authority to protect the Ukrainian lands from numerous enemies is dissonant with the anti-colonial narrative of the oppressed nation, in the Prologue. The discursive “non-alignment” of these plans is reflected in the compositionally unjustified retardation of the prologue (the scene of the mermaids` game), in the multiplicity of characters/images embodying sense of national resentment – the girl, Nalyvayko, Pavlyuk, Ostryanitsa, the oak tree, the Voice from under the stone, and the Spirit of Midnight. In the Prologue of Hrebinka’s poem “Bohdan”, the pathos of anti-colonial resentment prevails while it is re-extrapolated from Muscovy to Polish-Lithuanian Commonwealth for the sake of compromise. In this part of the poem, mythological features of poetics are determined by a mental unconscious desire for vengeance cultivated by Ukrainian (Pre)romanticism. The Prologue can be seen as a separate mini-poem about anti-colonial resentment, while in the main part of the poem, the search for a compromise between the national and imperial perspectives is pursued. In the main part of the poem, the elements of colonial poetics are present: 1) in the speeches of hetman Khmelnitskyi, who is ready to surrender his regalia to the Moscow tsar, 2) in the narrative emphasis on the cultural and religious closeness of Ukrainians and Muscovites, and 3) in the readiness of the community to submit to the (potential) imperial center as well as 4) in the ideological assertion of Moscow’s historically determined rule over Ukraine as a blessing for it. However, the final scene of the people`s decision to submit to the Moscow tsar can be interpreted both as a definitive victory of the pro-imperial colonial worldview and as a reproach to Moscow for the betrayed “brotherhood”, which is voiced by the author from a distance of time, similar to the corresponding scenes in Cossack chronicles and the literary works of Ukrainian Romanticism. In the historical plot of the poem, it has been recognized the fluctuation between anticolonial resentment redirected on the Ukrainian-Polish fighting and actualized as the reason for the rebellion led by Khmelnytskyi, and glorification of the Tsardom of Muscovy as the only ally and defender (in consonant with imperial doctrine and the XVIII century Ukrainian Chronicles based on it). The postcolonial deconstruction of the poem “Bogdan” by E. Hrebinka highlights the problem of balancing the artistic consciousness of the Romantic era between anti-colonial and colonial poetic coordinates. The intertextual juxtaposition of the poem with significant works of the time it was written as well as texts relevant to its author, demonstrates the typicality of the situation of ideological “duality” and reveals the extensive influence of imperial narratives and colonial stagnation on the Ukrainian literary process of that epoch. In Evhen Hrebinka’s poem “Bohdan”, the balancing between anti-colonial and colonial poetic strategies is driven by the authors’ (split) consciousness, the influences of romanticism cultural paradigm and Russian imperial doctrine as well. These multi-directional influences on writing are being deconstructed in the view of postcolonial studies. This approach can be helpful in understanding the threat of imperial propaganda framework in national cultural and literary process in the past. It is promising to further apply postcolonial methodology to texts from both the 18th and 19th centuries in order to gain a deeper knowledge of the specificity of the evolution of national self-consciousness and its reflection in literature.